Rap e identidade cultural: uma análise dos grupos Irmandade Rap Crato e Júnior Baladeira - Batista, Laelba Silva (2018)
Born on the suburbs of New York rap is a musical style well known worldwide. Together with other elements such as break (dance), the MC (master of ceremony), the graffiti (visual art), and the DJ (musical composure) we have what we now days call hip-hop. The fusion of DJ with MC generated the Rap, which means “rhythm and poetry.” Rapidly rap developed and was spread to all the world. It has become a symbol of juvenile resistance and struggles, and in each different place of the world rap presents different characteristics, baring the cultural framework of each location. The primary goal of this work was to understand the relationship between rap and the cultural identity of youngsters from the Irmandade Rap Crato (CE) e Júnior Baladeira (PE). The methodology used is based on a qualitative approach, using semi-structured interviews and participant observation. The analysis of the results was mainly supported by authors like Hall (2002), Giddens (2005), Pais (1996), Abramo (1997), Weller (2002), Kellner (2002), among others. The obtained results indicate that rap has been a proficuous space for discoveries and new identifications by the youngsters from both groups. In this sense, these young people had the chance to realize that they live in a culture of resistance facing an exclusionary system. Additionally, rap promoted the construction of local identities, becoming a space of re-signification of the cultural identity of the young.